Formação continuada e suas implicações no trabalho com a produção, correção e reescrita de textos - Bernardon, Dayse Grassi (2016)
Between December2010 and June 2015, a research project (from now on Obeduc Project) was developed linked to the research Language: linguistic, cultural and teaching practices, from the Graduation Program in Portuguese Language from Unioeste and Education Observatory (CAPES/INEP). This project focused the research in Western Paraná, more specifically, in seven municipalities which have indexes values below 5.0 on INEP/SAEB (Brazil Exam) evaluation in 2009. Its goal was to collect data with the teachers from basic education-early years, the 5th grade students greatest difficulties in relation to reading and writing to, from that, discuss through actions of Continuing Training, deepening the contents that involve reading, text production and rewriting teaching, since they were considered necessary according to the research. As a result, it was developed, in each municipality involved, between 2011 and 2012, 80 hours of continuing education in Portuguese Language. Once the goals were completed within the Obeduc Project, few questions emerged they were assumed by us this Doctorate research: How did teachers put into practice the subjects related to production, correction and texts rewriting worked into the continuing education process? What do the teachers (un) known about dealing with production practice, correction and textual rewriting? How do the collaborative actions of the researcher developed through reflective sessions focused on production, correction and textual rewrite can contribute with the practice of this content? To find answers, it was drawn, as general objective: To reflect on work with the production, correction and textual rewriting, resulting from an FC process and collaborative actions promoted by the researcher. From this moment on, we advocate a thesis in that FC actions, associated to collaborative research, using reflexive sections, promotes a greater involvement and, consequently, improves knowledge. For this, it was developed a research theoretically supported by dialogic and interacionist language approach (GERALDI, 1984; 2013[1991]; BAKHTIN/VOLOCHIVOV, 2004[1929]; 2010[1929]) and in theoretical and methodological assuptions that guide the text production (GERALDI, 1984, 2013[1991]; MENEGASSI, 2004, 2007, 2010a; COSTA-HÜBES, 2008, 2009, 2012a), among other authors. Yet, our research is supported by Applied Linguistics (MOITALOPES, 2006, FABRÍCIO, 2006; SIGNORINI, 1998), and also, in a qualitative and interpretivist approach (ANDRÉ, 1995; FLICK, 2008; BORTONI-RICARDO, 2008; among others); the ethnographic type as André (1995) supports; and collaborative, according to Cabral (2012), Bortoni-Ricardo (2008) and Ibiapina (2007) definitions. Four teachers operating in the fourth grade and fifth grade of elementary school of the municipality of Diamante do Oeste were the subjects of our research. The data surveying was possible through a diagnostic research (first stage of the survey) and collaborative research(second stage of the survey), having as the data-generating instruments the questionnaire, the interview with the focus group, the classes observation, the documental analysis and reflective sessions involving these teachers. With the analysis of the data obtained in diagnostic research, we returned to school, with the aim of, in a collaborative action through reflective sessions, discuss and work with teachers, subjects of the research, the main difficulties encountered. The results obtained showed that there is a necessity of more time for Continuing Education for teachers, but that it should happen in a distinct way from the current ones, because, the Continuing Education meetings, most of the time, do not reflect the knowledge shared and discussed, in the school routine. With this in mind, we highlight the importance of working through reflective thinking sections, in a cooperation research which allows a greater interaction between researchers and teachers in a way that, through discussions, knowledge could be rethought, reworked and rebuilt from the teaching practice, for better serving the language teaching and learning processes.